2018
DOI: 10.3126/jnps.v37i2.17028
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Dental Health Screening in Paediatric Office Practice

Abstract: Introduction: Dental health problems in children are often overlooked. Poor oral health negatively affects growth, learning, communication, self-esteem and rarely can also lead to serious fatal infection. Paediatrician can play key role in screening dental health problems. The objectives of this study were to screen children for dental caries in paediatric office and correlate with socio-demographic, dietary and oral hygiene risk factors.Material and Methods: After basic oral health training, paediatrician ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…In addition to the above, it is suggested that dental educators, administrators, and policy-makers in the fi eld of preventive dentistry and dental public health must focus their undergraduate and postgraduate curriculum towards redefi ning and restructuring the art of imparting dental education to the public, particularly to those with special health care needs (Kenney et al, 2008;DeMatt ei et al, 2012;Petrova et al, 2014). The current study, like many others previously published in dental literature, clearly elicits the need to revamp our educational strategy for the next generation of dental practitioners and specialists; to redirect their att ention towards a more inclusive system that lets healthcare professionals draw on the combined knowledge and resources in an att empt to improve disadvantaged communities like those with special needs, their caregivers and families (Waldman et al, 2001;DeMattei et al, 2012;Petrova et al, 2014;Dagli et al, 2017).…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…In addition to the above, it is suggested that dental educators, administrators, and policy-makers in the fi eld of preventive dentistry and dental public health must focus their undergraduate and postgraduate curriculum towards redefi ning and restructuring the art of imparting dental education to the public, particularly to those with special health care needs (Kenney et al, 2008;DeMatt ei et al, 2012;Petrova et al, 2014). The current study, like many others previously published in dental literature, clearly elicits the need to revamp our educational strategy for the next generation of dental practitioners and specialists; to redirect their att ention towards a more inclusive system that lets healthcare professionals draw on the combined knowledge and resources in an att empt to improve disadvantaged communities like those with special needs, their caregivers and families (Waldman et al, 2001;DeMattei et al, 2012;Petrova et al, 2014;Dagli et al, 2017).…”
Section: Discussionsupporting
confidence: 57%
“…The low statistics appear counter-intuitive in light of the well-documented need for such an integrated dental and comprehensive healthcare programme (DeMattei et al, 2012;Dagli et al, 2017;Kharbanda & Dhingra, 2017;Pathak, 2017;Mandic et al, 2018). While the numbers show a definite improvement from previous years in the form of revisits (from 5.2% across 2016-18 to 16% during the short 6-month study period), they are still disappointing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation